Histological correlates of gastro esophageal reflux disease in South Indian population - Ramasamy, Jawahar; Kurian, George; Varghese, Renu G’Boy; Alexander, Thomas (International Journal of Research in Medical Sciences, 2017)
Background: Diagnosing gastroeosopageal reflux disease (GERD) accurately is a complex problem. This study was conducted to examine the histological findings of GERD in Indian subjects. Esophageal biopsy can be combined with pH monitoring and endoscopy to define the histological damage that occurs due to acid regurgitation. The sensitivity and specificity of the individual findings needs clarity in this clouded area in order to be of use to the pathologist. Methods: A total of 102 patients with dyspepsia were included in this study. Those with heartburn and /or regurgitation were identified as patients with GERD and those without these symptoms were treated as cases of non GERD dyspepsia. Biopsies were taken 2cm above ’Z’ line in all cases. The biopsies were read by a single pathologist. Basal cell hyperplasia (BCH), neutrophilic exocytosis (NE), dilated intercellular spaces (DIS), papillary elongation (PE) and lymphoid aggregates (LA), necrosis (NEC) and eosinophilic infiltration were studied. Results: 68 patients had GERD dyspepsia and 34 had non GERD dyspepsia. The histological findings of BCH, NE, PE, DIS, LA were found to be found much more often in patients with GERD symptoms (p values ranged from 0.0001 to 0.0008). We found BCH and papillary elongation together were the most sensitive histological findings. Specificity was highest when DIS combined with NE. Conclusions: In this study we found basal cell hyperplasia is the most common histological finding, and when combined with DIS or papillary elongation enhances its sensitivity. However to exclude other causes of dyspepsia, a combination of DIS, PE and NE can be used effectively.